Autism Phenotypes in Tuberous Sclerosis Complex: Diagnostic and Treatment Considerations. (December 2015) - Gipson, Tanjala T.; Poretti, Andrea; Thomas, Emily A.; Jenkins, Kosunique T.; Desai, Sonal; Johnston, Michael V.
Tuberous sclerosis complex is a multisystem, chronic genetic condition characterized by systemic growth of benign tumors and often accompanied by epilepsy, autism spectrum disorders, and intellectual disability. Nonetheless, the neurodevelopmental phenotype of these patients is not often detailed. The authors describe 3 individuals with tuberous sclerosis complex who share common characteristics that can help to identify a distinct profile of autism spectrum disorder. These findings include typical cognitive development, expressive and pragmatic language deficits, and anxiety. The authors also describe features specific to tuberous sclerosis complex that require consideration before diagnosing an autism spectrum disorder. Identifying distinct profiles of autism spectrum disorder in tuberous sclerosis complex can help optimize treatment across the life span.